Knowledge, attitudes and practices of the Chinese public with respect to coronavirus disease (COVID-19): an online cross-sectional survey - Huiming Gao; Rujun Hu; Ling Yin; Xiaoli Yuan; Hao Tang; Lan Luo; Mei Chen; Di Huang; Ying Wang; Anyong Yu; Zhixia Jiang (BMC, 2020)
Abstract Background Coronavirus disease (COVID-19) has become a pandemic. The knowledge, attitudes, and practices (KAP) of the public play a major role in the prevention and control of infectious diseases. The objective of the present study was to evaluate the KAP of the Chinese public and to assess potential influencing factors related to practices. Methods A cross-sectional online survey was conducted in China in February 2020 via a self-designed questionnaire comprising 33 questions assessing KAP. Results For the 2136 respondents from 30 provinces or municipalities in China, the accurate response rate for the knowledge section ranged from 72.7 to 99.5%, and the average was 91.2%. Regarding attitude section, the percentage of positive attitudes ("strongly agree" and "agree") ranged from 94.7 to 99.7%, and the average value was 98.0%. The good practices ("always" and "often") results ranged from 76.1 to 99.5%, and the average value was 96.8%. The independent samples t-test revealed that gender and ethnic differences had no effect on knowledge, attitude or behaviour (P > 0.05). However, knowledge was associated with age (t = 4.842, p < 0.001), marital status (t = − 5.323, p < 0.001), education level (t = 8.441, p < 0.001), occupation (t = − 10.858, p < 0.001), and place of residence (t = 7.929, p < 0.001). Similarly, attitude was associated with marital status (t = − 2.383, p = 0.017), education level (t = 2.106, p = 0.035), occupation (t = − 4.834, p < 0.001), and place of residence (t = 4.242, p < 0.001). The multiple linear regression analysis results showed that the factors influencing practices were knowledge (t = − 3.281, p = 0.001), attitude (t = 18.756, p < 0.001), occupation (t = − 3.860, p < 0.001), education level (t = 3.136, p = 0.002), and place of residence (t = 3.257, p = 0.001). Conclusions The Chinese public exhibited a good level of knowledge of COVID-19, a positive attitude, and high adherence to good practices. COVID-19-related knowledge, attitudes and practices were affected by age, marital status, education level, occupation, and place of residence to varying degrees. In addition, practices were affected by knowledge and attitudes towards COVID-19.